Tyd as gawe - God se tyd: die polsslag van die kerkjaar - E. Kloppers (Acta Theologica)
When seen as a gift – as God’s time – the careful shaping of the church year strengthens the celebratory character of the worship service; contributes to the effective proclamation of the Word; underlies the church’s confession; introduces new people and young people to the faith; forms community; adds to comforting people; exerts healing; anchors the church’s diaconal work; contributes to missionary proclamation to “outsiders”; and reflects the ecumenical character of the church service. This article is a plea for a greater consciousness for the structure and times of the church year, with a view to the conveyance of the full truth of the Gospel and the formative effect in the life of the community of faith.